A dual-channel, curved-crystal spectrograph for petawatt laser, x-ray backlighter source studies - Theobald, W; Stoeckl, C; Jaanimagi, P; Nilson, P; Storm, M; Meyerhofer, D; Sangster, T; Hey, D; MacKinnon, A; Park, H; Patel, P; Shepherd, R; et al. (2009)
A dual-channel, curved-crystal spectrograph was designed to measure time-integrated x-ray spectra in the ∼1.5 to 2 keV range (6.2-8.2 Å wavelength) from small-mass, thin-foil targets irradiated by the VULCAN petawatt laser focused up to 4× 10 20 W/ cm 2. The spectrograph consists of two cylindrically curved potassium-acid-phthalate crystals bent in the meridional plane to increase the spectral range by a factor of ∼10 compared to a flat crystal. The device acquires single-shot x-ray spectra with good signal-to-background ratios in the hard x-ray background environment of petawatt laser-plasma interactions. The peak spectral energies of the aluminum He α and Ly α resonance lines were ∼1.8 and ∼1.0 mJ/eV sr (∼0.4 and 0.25 J/Å sr), respectively, for 220 J, 10 ps laser irradiation. © 2009 American Institute of Physics.